2009
DOI: 10.1128/aac.00872-08
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Evaluation of Liposomal Amikacin for Inhalation in Cystic Fibrosis Patients with Chronic Pseudomonal Infection

Abstract: The pharmacokinetics and pharmacodynamics of a novel liposomal amikacin for inhalation were evaluated in cystic fibrosis patients with chronic pseudomonas infection. Twenty-four patients from two studies received 500 mg of liposomal amikacin by inhalation once daily for 14 days. Serum, sputum, and 24-h urine samples were collected on days 1 and 14 of therapy; pulmonary function tests (PFT) and sputum for quantitative microbiology were assessed at baseline and serially for 14 days. Relationships between amikaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 6 publications
(7 reference statements)
5
46
1
2
Order By: Relevance
“…Amikacin concentrations in sputum were about 45-fold higher upon aerosolized administration of 500 mg of a liposomal formulation than after parenteral administration of 30 mg/kg of body weight; mean sputum concentrations increased ϳ3-to 5-fold from day 1 to day 14 (170,171). In supplemental material published previously (158), it was reported that mean serum concentrations as low as 1.29 g/liter and mean sputum concentrations of 2,286 g/g were recorded following aerosolized administration of 560 mg (171).…”
Section: Serum and Sputum Pharmacokineticsmentioning
confidence: 99%
“…Amikacin concentrations in sputum were about 45-fold higher upon aerosolized administration of 500 mg of a liposomal formulation than after parenteral administration of 30 mg/kg of body weight; mean sputum concentrations increased ϳ3-to 5-fold from day 1 to day 14 (170,171). In supplemental material published previously (158), it was reported that mean serum concentrations as low as 1.29 g/liter and mean sputum concentrations of 2,286 g/g were recorded following aerosolized administration of 560 mg (171).…”
Section: Serum and Sputum Pharmacokineticsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Targeted pulmonary delivery of antimicrobials (ie, antibacterials and antifungals) by inhalation aerosols is the subject of much recent interest in research and development, including several clinical trials. [8][9][10][11] Pulmonary liposomal aerosol delivery of antimicrobials can effectively fight infections, [14][15][16][17] and these liposomal delivery systems can be rendered into inhalable dry powder aerosols. 18 MOXI has been encapsulated in glutaraldehyde-crosslinked chitosan microspheres for intrapulmonary administration.…”
Section: Introductionmentioning
confidence: 99%
“…Arikace is a liposomally encased preparation of amikacin, providing sustained release and rapid delivery times. Arikace has completed phase 2 trials, 2,8 reporting relative improvement in FEV 1 of 10.8% at 7 days with 500 mg inhaled once per day , and a phase 3 trial will soon be recruiting subjects with CF and P aeruginosa . 9 Another trial not specifi cally for patients with CF is also listed for subjects with nontuberculous mycobacteria and is recruiting.…”
Section: Antiinfl Ammatory Treatmentsmentioning
confidence: 99%